EphA2-Dependent Internalization of A. fumigatus Conidia in A549 Lung Cells Is Modulated by DHN-Melanin - Keizer, Esther M.; Wösten, Han A. B.; de Cock, Hans (Frontiers in Microbiology, 2020)
Dectin-1 and EphA2 receptors recognize β-glucan present in the fungal cell wall. Inhibition of Dectin-1 with the monoclonal 2a11 antibody was shown to reduce internalization of conidia of the human pathogen Aspergillus fumigatus into epithelial cells. In this study we investigated the role of EphA2 receptor present on A549 epithelial type II lung cells in the interactions with A. fumigatus conidia. We assessed whether EphA2 was involved in association and internalization of conidia and in the initiation of the immune response by using the kinase inhibitor dasatinib. In addition, we used an EphA2-specific antibody to assess the role of EphA2 in conidial internalization. A 50% reduction of internalization of conidia was observed when this receptor was blocked with either dasatinib or the EphA2-specific monoclonal antibody, which was similar when Dectin-1 was inhibited with the 2a11 monoclonal antibody. Inhibition of both receptors reduced the internalization to 35%. The initiation of the immune response, as measured via secretion of IL-8, was also reduced after EphA2 inhibition with dasatinib. EphA2 inhibition was also assessed in a hydrophobin deletion strain (∆rodA) that exposes more β-glucan and a DHN-melanin deletion strain (∆pksP) that exposes more glucosamine and glycoproteins. The ∆rodA strain behaved similar as the wild-type strain with or without EphA2 inhibition. In contrast, the ∆pksP mutant showed an increase in association to the A549 cells and a decrease in internalization, irrespective of EphA2 inhibition. These results show that the internalization of A. fumigatus conidia into A549 lung cells depends on the activation of the EphA2 receptor and that DHN-melanin affects both the association and internalization of conidia into A549 epithelial lung cells.